Annealing Effect on the Microstructure and Mechanical Properties of AA 5182 Aluminum Alloy - Filizzola,Daniel Marinho (2021)
Abstract The properties of aluminum alloys can be improved by the processing conditions that cause changes in the microstructure and by the addition of alloy elements. In order to understand the physical behavior and mechanical properties of aluminum alloys, it is important to be aware of some of the microstructural characteristics. Some of these characteristics are the morphology, alloy elements, volume and size, and second phase. In this study, we analyzed the effect of annealing on the mechanical and microstructural properties of the laminated AA 5182 aluminum alloy, when subjected to different annealing conditions. The alloy was heated to temperatures of 50º C, 100º C, 150º C, 200º C, 250º C and 300º C for 10 minutes and left to cool naturally. The evolution of the microstructure was characterized by optical and electronic microscopy with EDS, and, to obtain the mechanical properties, a tensile test was performed and the fractures were subsequently analyzed. The results showed that the heat treatment used reduced the amount of second phase particles and this influenced the mechanical properties.